Crystal structure of (E)-4-(6-(4-(2-(pyridin-4-yl)vinyl)phenoxy)pyrimidin-4-yl)morpholine, C21H20N4O2 - Bai Su-Fen; Liu Jia-Xuan; Li Shan-Shan; Tian Chun-Yu; La Xiao-Jin (Zeitschrift für Kristallographie - New Crystal Structures)
C21H20N4O2, triclinic, P1‾$\overline{1}$ (no. 2), a = 5.874(3) Å, b = 16.526(7) Å, c = 20.147(8) Å, α = 67.140(5)°, β = 83.287(6)°, γ = 86.910(6)°, V = 1789.7(14) Å3, Z = 4, Rgt(F) = 0.0614, wRref(F2) = 0.1675, T = 296 K.